Influences of sudden changes in discharge and physical stream characteristics on transient storage and nitrate uptake in an urban stream. Issue 6 (1st August 2014) - Mueller Price, Jennifer; Bledsoe, Brian P.; Baker, Daniel W.
Abstract Changes in the physical structure of urban streams can occur abruptly due to flashy high‐flow events and subsequently alter stream processes, including transient storage and nitrate uptake. We examined temporal variability in transient storage and nitrate uptake by exploring the effects of altered physical characteristics resulting from a single high‐flow event in three reaches of Spring Creek, an urban stream in Fort Collins, Colorado, USA. Study reaches of varying geomorphic and hydraulic characteristics were chosen to represent distinct geomorphic settings in terms of substrate size, sinuosity, bed slope, and degree of rehabilitation and structural controls. We performed detailed physical characterizations and multiple nutrient injections of Br− and NO3− to estimate transient storage and nitrate uptake in each reach. A comparison of pre‐flood and post‐flood data indicates that transient storage and nitrate uptake are highly context specific and mediated by interactions between geomorphic setting and flood discharge. In the two reaches that showed significant post‐flood increases in transient storage (250% to 350% increases in Fmed200), the pool‐riffle reach exhibited a significant increase in uptake velocity, while the channelized reach did not. In contrast, transient storage decreased post‐flood in the third reach containing hydraulic structures. These complex responses likely reflect reach‐specific differences in hyporheic versus in‐channel storage. This study shows that repeat injections are necessary to describe nutrient dynamics because transient storage and nitrate uptake can be highly variable over time (showing changes on the order of 100%) due to variation in discharge and geomorphically influential flow events. Copyright © 2014 John Wiley & Sons, Ltd.